The GnRH analogue dephereline given in a fixed-time AI protocol improves ovulation and embryo survival in dairy cows. (February 2019) - Garcia-Ispierto, I.; De Rensis, F.; Pérez-Salas, J.A.; Nunes, J.M.; Pradés, B.; Serrano-Pérez, B.; López-Gatius, F.
Abstract: This study compares the fertility effects of inducing ovulation using the GnRH analogue, dephereline, versus natural GnRH at the end of a 5-day progesterone(P4)-based protocol for fixed-time artificial insemination (FTAI) in in heat-stressed and non-heat stressed lactating dairy cows. Cows were given GnRH (GnRH group, n  = 369) or dephereline (DEPH group, n  = 379) and were inseminated 14–20 h later. Dephereline treatment increased corpus luteum (CL) size on Day 7 post-AI compared with GnRH ( P  < .0001) while a one-mm increase in CL size was found to give rise to a 1.1-fold increase in the pregnancy rate at FTAI ( P  = .001). Based on odds ratios, the interaction between treatment and heat stress had a significant effect on the ovulation failure rate ( P  < .01). This meant that relative to non-heat-stressed GnRH-treated cows, ovulation failure was 2.9 times more likely in heat-stressed GnRH-treated cows ( P  = .001), 0.3 times less likely in non-heat-stressed DEPH-treated cows ( P  = .04) and was similar in heat-stressed DEPH-treated cows. Further, non-heat-stressed DEPH-treated cows were more likely to conceive by a factor of 1.6 than the remaining cows ( P  = .03). Finally, GnRH-treated multiparous cows were 9.9 times more likely to suffer pregnancy loss than the remaining cows ( P  = .03). Our results indicate that, compared to treatment with GnRH, dephereline reduced the risk of ovulation failure and consequently increased the pregnancy rate under heat stress conditions. In multiparous cows, dephereline treatment also reduced the negative age effect on pregnancy maintenance. Highlights: Compared to GnRH, dephereline favored ovulation under heat stress conditions. Dephereline returned a higher pregnancy rate in heat-stressed cows than GnRH. Dephereline treatment reduced the pregnancy loss rate in multiparous cows.